2019
DOI: 10.1038/s41419-019-2149-1
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-educated mesenchymal stem cells promote the survival of cancer cells at primary and distant metastatic sites via the expansion of bone marrow-derived-PMN-MDSCs

Abstract: Bone marrow mesenchymal stem cells (BMSCs) are multipotent stromal cells that can differentiate into a variety of cell types. BMSCs are chemotactically guided towards the cancer cells and contribute to the formation of a cancer microenvironment. The homing of BMSCs was affected by various factors. Disseminated tumour cells (DTCs) in distant organs, especially in the bone marrow, are the source of cancer metastasis and cancer relapse. DTC survival is also determined by the microenvironment. Here we aim to eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 43 publications
6
37
0
Order By: Relevance
“…In rhabdomyosarcoma, where MDSCs of the CXCR2+ CD11b+ Ly6G high phenotype mediated local immune suppression, the efficacy of antibodies directed to PD-1 was augmented when tumor-bearing mice had myeloid cells deficient in CXCR2 (123). Essentially similar findings were noted in a mouse model of lung cancer, where PMN-MDSCs reduced T cell proliferation, and treatment of mice with antibodies to CXCL5-which is a key chemoattractant of such MDSCs-has reduced the proportion of PMN-MDSCs and elevated the efficacy of anti-PD-L1 in increasing the survival of mice (124).…”
Section: Atypical Chemokine Activities Exerted At the Tumor Microenvisupporting
confidence: 57%
“…In rhabdomyosarcoma, where MDSCs of the CXCR2+ CD11b+ Ly6G high phenotype mediated local immune suppression, the efficacy of antibodies directed to PD-1 was augmented when tumor-bearing mice had myeloid cells deficient in CXCR2 (123). Essentially similar findings were noted in a mouse model of lung cancer, where PMN-MDSCs reduced T cell proliferation, and treatment of mice with antibodies to CXCL5-which is a key chemoattractant of such MDSCs-has reduced the proportion of PMN-MDSCs and elevated the efficacy of anti-PD-L1 in increasing the survival of mice (124).…”
Section: Atypical Chemokine Activities Exerted At the Tumor Microenvisupporting
confidence: 57%
“…Among the various immune cells infiltrating the pre-metastatic microenvironment, our multifaceted results suggest MDSCs as the key determinant in forming the pre-metastatic microenvironment. Consistent with previous studies ( 47 , 48 ), MDSCs showed great power in promoting liver metastasis, and MDSCs depletion might reverse the metastasis. However, other cell types are also indispensable.…”
Section: Discussionsupporting
confidence: 92%
“…As the precursor cells of dendritic cells (DCs), macrophages, and granulocytes, MDSCs can significantly suppress immune cell responses. It is well known that the number of MDSCs in cancer patients is higher than that in the healthy population (29)(30)(31). This is because MDSCs in the peripheral blood increase and accumulate locally in the tumor and will release active substances to suppress the immune response and promote tumor growth.…”
Section: Discussionmentioning
confidence: 99%